MathMarvel 3.0 / Nadiah Mohamed ... [et al.]. - Mohamed, Nadiah; Othman, Norlida; Andu, Yusrina; Yaacob, Nurul Aityqah; Mohd Ruslan, Siti Zaharah; Ahmad, Siti Noor Dina (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The "MathMarvel 3.0" program took place at UiTM Negeri Sembilan's Kuala Pilah Campus from January 3 and January 10, 2025. It involved 216 students and 6 facilitators from a variety of academic backgrounds. The event aimed to enhance peer tutoring and exam skills through diverse question-solving methodologies due to high failure rate in math subject. Participants reported improved learning and facilitator skills, with greater confidence and enjoyment. Despite these successes, challenges such as identifying subject-specific facilitators and monitoring students' attendance were noted. To maintain educational momentum and address these issues, it is recommended that the program be held regularly each semester. Regular offerings will assist the Department of Mathematical Sciences Studies in improving student performance and reducing failure rates.